Strategi Mahasiswi Kelas E1 PAI Dalam Menghadapi Tantangan Akademik - Brasa, Ayu Astuti; Amini, Khumairoh; Siregar, Pani Akhiruddin (Journal of Sustainable Education, 2025)
Female students enrolled in the Islamic Religious Education (PAI) program face a range of complex academic challenges in today’s educational landscape. These include high academic demands, time constraints, psychological pressure, and limited access to knowledge. This study aims to explore and analyze the strategies employed by female PAI students in Class E1 Morning to navigate these academic challenges. Utilizing a qualitative research method with a case study approach, data were gathered through in-depth interviews, observations, and documentation. The participants consisted of three sixth-semester PAI students at Universitas Muhammadiyah Sumatera Utara. The findings reveal that the most commonly adopted strategies include priority-based time management, the internalization of Islamic values, strong learning motivation, and seeking social support from both the university and their families. Additionally, students implemented various other approaches, such as forming study groups, leveraging information technology, and enhancing interpersonal skills. The effectiveness of these strategies is further influenced by intrinsic motivation and a supportive learning environment. The results of this study are expected to contribute to the development of academic support services tailored to the needs of female PAI student.